Insights and Challenges about the use of VNA on Airport/Hinterland Linkages - Emilia Baltazar; José Braz; Jorge Silva; Margarida Vaz (European Regional Science Association (ERSA), 2011)
Airport operators, planners and regulatory agencies to measure the economic contribution of an airport to its local and regional surroundings, frequently use economic impact studies. The most common methods to measure airport economic impacts have been the Input-Output method, the Collection of Benefits method and most recently the Catalytic method. The most used measured variables include employment, wages, local and regional spending and air traffic levels. This paper is a new approach to these impact studies in which is used a new tool to identify the added values generated within airports and surrounding community interactions to better catch real socio-economic impacts. The VNA - Value Network Analysis, is used as an integrated methodology to identify these interactions and added values generated (tangibles and intangibles) in the business system of landside airports. To define the system it is used the matrix key airport performance benchmarking areas of ACI (Airport Council International) that are in the range of landside of the airport.
Keywords: 330; Social Networks; Airport Landside; Value Network Analysis; Key Performance Indicators; Business System